2003
DOI: 10.1002/eji.200323375
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor‐mediated tyrosine phosphorylation of paxillin via MyD88‐dependent and ‐independent pathways

Abstract: Toll-like receptor (TLR)-mediated recognition of pathogens represents one of the most important mechanisms of innate immunity. A proximal signaling event of TLR is the direct binding of an adaptor protein MyD88 to TLR and recruitment of the IL-1R-associated kinase (IRAK). In the present study, we examined the effect of several TLR ligands on protein tyrosine phosphorylation in rat macrophages. Macrophage-activating lipopeptide-2 kDa (MALP2) and lipoarabinomannan were used as activators of TLR2, while lipopolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 41 publications
6
48
0
Order By: Relevance
“…RAFTK/pyk2 activity and/or paxillin phosphorylation depends upon Src (35,41) because Src kinase inhibitors prevent increased phosphorylation of RAFTK/pyk2 as well as paxillin (42). Our results are consistent with RAFTK/pyk2-mediated loss of paxillin promoting apoptotic signaling by promotion of Src kinase activity.…”
Section: Discussionsupporting
confidence: 85%
“…RAFTK/pyk2 activity and/or paxillin phosphorylation depends upon Src (35,41) because Src kinase inhibitors prevent increased phosphorylation of RAFTK/pyk2 as well as paxillin (42). Our results are consistent with RAFTK/pyk2-mediated loss of paxillin promoting apoptotic signaling by promotion of Src kinase activity.…”
Section: Discussionsupporting
confidence: 85%
“…We further demonstrated that other TLR ligands may also induce FAK phosphorylation at Tyr 397 and require FAK for cytokine release because comparable results have been obtained with the TLR2 ligand Pam 3 CSK 4 (data not shown). Also, our findings extend to FAK the observation that TLR2 and TLR4 agonists induced tyrosine phosphorylation of the prolinerich tyrosine kinase 2 (Pyk2), which in turn increases tyrosine phosphorylation of paxillin, an adaptor protein involved in integrin signaling and binding to Pyk2, vinculin, and FAK, through MyD88-dependent and -independent pathways (19). However, in our experiments, MyD88 does not seem to be essential for FAK autophosphorylation because this kinase is phosphorylated in MyD88 Ϫ/Ϫ macrophages activated with either LPS or protein I/II.…”
Section: Discussionsupporting
confidence: 70%
“…Phosphatase treatment established that the slower migrating form of Mal represented tyrosine-phosphorylated Mal. A role for tyrosine phosphorylation has previously been ascribed to the TLR2 and TLR4 signaling pathway (32,33). In this study, MALP-2 and LPS rapidly triggered tyrosine phosphorylation of endogenous Mal in THP-1 cells.…”
Section: Discussionsupporting
confidence: 48%